Blue genes, green promises: linking marine gene patents to biotechnology and sustainable development - Erik Zhivkoplias; Paul Dunshirn; Jean-Baptiste Jouffray; Marcel Jaspars; Robert Blasiak (Frontiers in Marine Science, 2026)
Marine genetics play an essential role in biodiversity studies, ecosystem monitoring, and biotechnology, yet little is known about how marine genetic sequences are translated into commercial applications. Although international frameworks such as the BBNJ Agreement and the Convention on Biological Diversity address access and benefit sharing, effective implementation requires empirical insight into how marine genes are used. Here we analyze the Marine Bioprospecting Patent Database, a global catalog of marine-derived genes appearing in patents, by combining structural topic modeling and large language model-assisted classification of 1,676 patent texts to map technological themes and actor contributions across healthcare, agriculture, industrial, and foundational biotechnology. Private-sector filings prioritize industrial and agricultural applications, whereas research institutes and governmental actors disproportionately contribute foundational, cross-cutting tools that enable downstream innovation. A curated subset of 221 patent claims mentioning marine enzymes illustrates applications ranging from bioenergy and green chemistry feedstocks to diagnostics and therapeutics. While many inventions align with sustainability objectives, others deliver incremental gains or support applications with ambiguous, if not adverse, environmental implications. Targeted policy, funding, and stewardship are needed to maximize net sustainability benefits and ensure equitable benefit-sharing under international frameworks.